Islamisasi Melalui Budaya - Rosmatami, Rosmatami (Al-Hikmah, 2012)
This paper aims at explaining the Islamization conducted through cultural form. Using descriptive method, this research tries to illustrate three froms of Islamization through literary from conducted in Indonesia during pre-colonization, colonization and modernization. The Islamization during pre-colonialisation was marked by the rise of literary from adapted from Middle East or from local tradition. In the second period, during colonial period, literary from occurred as the response of political struggle between the colonizer and colonized. This condition continued after the colonization ended. Yet, the rise of literature which has Islamic background nowadays seems to be a new phenomenon. How is this new phenomena explained?